Expansion of pipeless drainage functions for draining poorly permeable soils - Shtykov Valeriy; Yanko Yu.G.; Kantsiber Juryi; Ponomarev Andrey (E3S Web of Conferences, 2023)
Due to climate change, in the next 30-50 years, an increase in precipitation during the growing season is predicted in the Non-Chernozem zone of Russia. However, even now, traditional methods of draining poorly permeable soils in a number of cases have proved to be ineffective due to the insufficiency of operational and capital measures to accelerate the removal of surface water and the weak hydraulic connection between the arable layer and drains. The experience of operation of drainage systems in the Nonchernozem zone of Russia has shown that at large distances between channels, the removal of surface runoff is difficult. A rational solution is to reduce the distances between the conductive channels. In this case, instead of open collectors, we propose to use cavityless collectors for drainage, which do not interfere with the movement of heavy agricultural machinery. A complete analysis of the functioning of cavityless collectors has been carried out. In the part of hydrology, accounting for the increase in precipitation is discussed and a method is given for calculating the maximum average daily module of drainage flow for the early spring and summer-autumn periods. A geotechnical calculation of the settlement during the passage of a heavy general-purpose tractor of the 5th traction class K-744R1 (Kirovets) was performed. It is shown that under the design conditions, the settlements will be about 1 cm. An example of a hydraulic calculation of the reservoir with the calculation of the initial and maximum depth of the filtration flow in it is given. Hydraulic calculation is carried out according to a proven method, the theoretical foundations of which were developed by the authors in previously published articles. An important feature is that all possible filtration modes are taken into account in the hydraulic calculation: laminar, transitional and turbulent.